The impact of writing tutoring sessions on students registered in English Composition, and English Composition II of The Bachelor of Arts in Modern Languages Specialization in French and English, and English Teaching at The Foreign Language Department, semester I-2018 - Muñoz Martínez, Diego Adonay
Writing is one of the most important skills to be mastered at any level of education and it requires a lot of training. the challenge becomes more intense when someone studies a second or a foreign language. to learn how to write well requires not a lot of dedication but plenty of practice as well. in the foreign language department of the university of el salvador, some teachers have started suggesting writing centers or programs focused on the areas of writing because they consider that most of the students that start to study a language in the university of el salvador have a basic knowledge and poor communication skills.